O trabalho como princípio educativo em um assentamento de reforma agrária - Nagela Aparecida Brandao (2011)
The object of this research is educational practices developed on a land reform settlement in Minas Gerais understood as practices that develop in production and relations engendered by it. From the understanding of the concrete meaning and historically determined the work in the settlement, we sought to further clarify how to establish this relationship. Given the complexity of the subject and the set of variables that should be taken into account at the time of field research, we chose to focus the educational practices built into productive context, the labor process. The researched settlement was chosen to be one of the first created in the state of Minas Gerais, the result of first occupation held by the Rural Landless Workers Movement (Movimento dos Trabalhadores Sem Terra MST) in 1988 and have significant experience in solving the production problem by creating a cooperative agricultural production. The technical procedures for collection and analysis of data involved the literature survey as well as interviews and site visits that allowed grasp the object of study in its various dimensions. We did observations in the settlement, semistructured interviews with settlers and technical workers by INCRA MG - National Institute of Colonization and Land reform - and analysis of documents produced by INCRA-MG, universities. The study showed that the nesting process of socialization and education of human beings based on collective work and cooperative was a kind of laboratory where new personal relations based on solidarity and collective decision-making could be experienced. However, the every kind of dominant capitalist social relations imposed limits to the development of experience placing the question of whether or not to build socialism without a profound transformation of society as a whole, without constituting a new kind of state. Its possible to say that from experience of the cooperative, the work had a deeply educative character because it managed the technical formation allied to ruling political formation.